Representasi Pelanggaran Ham Akibat Korupsi dalam Film Dokumenter “Dirty Vote”: Analisis Kualitatif Perspektif Konstitusi - Mokhammad Aqil Al imdad; Romi Faslah (Jurnal Hukum Lex Generalis, 2026)
Dirty Vote, directed by Dandhy Dwi Laksono before the 2024 Indonesian election, became a significant alternative media phenomenon with millions of viewers within one day. This study examines representations of structural human rights violations in the documentary using constitutionalism, Thomas Pogge’s structural human rights theory and Habermas’s public sphere framework. The research applies qualitative methods through Fairclough’s critical discourse analysis, Pan and Kosicki’s framing model and Peirce’s semiotics. The findings reveal allegations of regulatory manipulation, bureaucratic politicization, misuse of social assistance funds and state apparatus mobilization that undermine popular sovereignty and simultaneously function as alternative public oversight mechanisms for democracy. These findings indicate that the film functions not only as a cultural product but also as an instrument of political criticism that expands public participation in monitoring the democratic process.